Kinetics of elemental sulfur reduction by petroleum hydrocarbons and the implications for hydrocarbon thermal chemical alteration. (15th April 2019) - Ellis, Geoffrey S.; Zhang, Tongwei; Kralert, Paul G.; Tang, Yongchun
Abstract: Although sulfur-containing compounds are known to play a significant role in the diagenic and catagenic processes that generate oil and gas, relatively little is known about the kinetics of reactions between elemental S and petroleum hydrocarbons. To investigate this subject, a series of closed-system pyrolysis experiments using paraffin, a low-sulfur oil, and a high-sulfur oil with and without elemental S were conducted, and first-order chemical kinetics were fit to the experimental results. The average value for the activation energy required to reduce elemental S to H2 S and to thermochemically alter higher molecular weight hydrocarbons to methane was calculated to be 193 kJ mol −1 (46 kcal mol −1 ). The results of this study demonstrate that under typical geologic conditions the rate of reduction of elemental S to H2 S by petroleum hydrocarbons is quite rapid. The maximum time for substantial amounts of elemental S to persist in contact with petroleum hydrocarbons is estimated to be no more than a few million years in cool reservoirs (e.g., <80 °C), and in hotter reservoirs (e.g., >120 °C) the half-life of elemental S may be as short as hundreds of years. Additionally, the presence of elemental S substantially lowers the onset temperature of hydrocarbon thermal chemical alteration (TCA). The activation energy for TCA of a low-sulfur oil to generate methane is estimated to be lowered by 92 kJ mol −1 (22 kcal mol −1 ) due to the presence of elemental sulfur. Consequently, the presence of elemental S in petroleum reservoirs is expected to lower the thermal stability of oil and decrease the maximum depth at which oil occurs within a basin (thermal deadline). The observed acceleration of hydrocarbon TCA is possibly due to organic sulfur compounds (e.g., thiols and sulfides) that form through the reaction of H2 S or polysulfides with hydrocarbons and subsequently thermally degrade leading to the formation of sulfur radicals that in turn enhance TCA reactions.